The Ex Ante and Ex Post Price Effects of Quarterly Earnings Announcements Reflected in Option and Stock Prices - Patell, James M.; Wolfson, Mark A. (Journal of Accounting Research, 1981)
James M. Patell, Mark A. Wolfson, The Ex Ante and Ex Post Price Effects of Quarterly Earnings Announcements Reflected in Option and Stock Prices, Journal of Accounting Research, Vol. 19, No. 2 (Autumn, 1981), pp. 434-458